2018
DOI: 10.1111/cea.13190
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome: A likely target for the treatment of allergic diseases

Abstract: Allergic diseases, such as asthma, rhinitis, dermatitis, conjunctivitis, and anaphylaxis, have recently become a global public health concern. According to previous studies, the NLRP3 inflammasome is a multi-protein complex known to be associated with many inflammatory conditions. In response to allergens or allergen/damage-associated molecular signals, NLRP3 changes its conformation to allow the assembly of the NLRP3 inflammasome complex and activates caspase-1, which is an evolutionarily conserved enzyme tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 128 publications
(142 reference statements)
2
53
0
Order By: Relevance
“…Classical studies show that activation of NLRP3 inflammasome consists of initial priming which upregulates the components of inflammasome, and then activation signal that promoting the assembly of inflammasome and the formation of persistent chronic inflammation . In our study, both LPS + CTPE and CTPE exposure promoted the expression of NLRP3 and the combination of NLRP3 and caspase‐1, indicating the important role of NLRP3 inflammasome in the transformation of LPS + CTPE‐ or CTPE‐induced BEAS‐2B cells . Moreover, we found that LPS + CTPE exposure upregulated the mRNA and protein levels of NLRP3 in comparison to the cells exposed to LPS or CTPE.…”
Section: Discussionsupporting
confidence: 68%
“…Classical studies show that activation of NLRP3 inflammasome consists of initial priming which upregulates the components of inflammasome, and then activation signal that promoting the assembly of inflammasome and the formation of persistent chronic inflammation . In our study, both LPS + CTPE and CTPE exposure promoted the expression of NLRP3 and the combination of NLRP3 and caspase‐1, indicating the important role of NLRP3 inflammasome in the transformation of LPS + CTPE‐ or CTPE‐induced BEAS‐2B cells . Moreover, we found that LPS + CTPE exposure upregulated the mRNA and protein levels of NLRP3 in comparison to the cells exposed to LPS or CTPE.…”
Section: Discussionsupporting
confidence: 68%
“…In addition to the Th2 response, a Th17 response is associated with asthma, notably severe glucocorticoid‐resistant asthma . From various studies of human diseases and mouse models, the elevation of IL‐1β and IL‐18 is associated with the development of allergic diseases, such as asthma, dermatitis, rhinitis, and conjunctivitis . All these events are connected with inflammasome activation and suggest participation of the inflammasome in the development and progression of asthma.…”
Section: Inflammasomementioning
confidence: 99%
“…As a member of the cysteine-aspartic acid protease family, caspase-1 is activated through the cleavage of pro-caspase-1 (25). In response to allergens or associated molecular signals, the NLRP3 inflammasome complex will be assembled and activate caspase-1, which proteolytically cleaves other proteins including the precursor of IL-1β (26). Our investigation has unraveled irisflorentin can reduce the secretion of pro-inflammatory cytokines including TNF-α, IL-1β and IL-6 in RBL-2H3 cells stimulated by DNP-HSA.…”
Section: Discussionmentioning
confidence: 80%